International division of labour and regional development - "Misra , R . P (ed.)" (New Delhi, 1989)
While the Potsdam Declaration of 1945 aimed at the demilitarization, democratization and decentralization of Japan, the occupation authorities under Gen. Mac Arthur effected a large number of sweeping changes in almost all areas of Japanese national life. Although the Japanese progressive groups hailed the GIs as liberators, the conservative government, which saw these reforms as alien to the national character, was ever trying to thwart them. This book centres around the several U.S. attempts between 194749 at a peace treaty with Japan against the backdrop of super power rivalry in the Pacific region and presents the views of political leaders in the opposition and the government in Japan and those of other countries as well as the views of Japanese intellectuals. Already in use as material for courses on Japanese foreign policy in the Karnataka and Gulabarga universities, this book could be gainfully adopted by students of international relations, are studies, Japanese history, government and foreign policy and as support material for the study of super power diplomacy in East Asia.
Keywords: International Organization